Transformasi Digital pada UMKM: Penggerak Pertumbuhan Ekonomi dan Inklusi di Negara Berkembang - Bahasoan, Awal Nopriyanto; Nur Qamariah S; Wahdaniah; Indayani B; Maghfirah Sari Azis (Indra Institute Research & Publication, 2025)
Digital transformation has become a crucial driver of economic growth, especially in developing countries, playing a significant role in empowering Micro, Small, and Medium Enterprises (MSMEs). This article explores how MSMEs’ adoption of digital technology accelerates economic inclusion, enhances competitiveness, and fosters sustainable growth. Using a Systematic Literature Review (SLR) approach, this study identifies key factors influencing successful digital transformation, including access to technology, digital literacy, and policy support. The analysis reveals that MSMEs adopting digital transformation experience increased productivity, expanded market reach, and greater access to financial resources. However, challenges such as limited infrastructure and digital skill gaps remain significant barriers. This study provides strategic insights for policymakers and industry players to optimize the benefits of digital transformation in the MSME sector as a primary driver of inclusion and economic growth